Tumor lesions in the oral region: verrucous carcinoma and oral squamous cell carcinoma. A case report - García Gutiérrez, Carlos Fernando (2022)
Oral squamous cell carcinoma represents a worldwide public health problem. Being the most common malignant neoplasm in the oral cavity and one of the ten most common cancers worldwide. Verrucous carcinoma is a variant of oral squamous cell carcinoma that has a high degree of local invasion and low possibility of spreading. In addition, it represents 2 to 12% of all oral carcinomas, with a 5-year survival rate. This article reports the case of a 79-year-old male patient, after performing the extra and intraoral exams, as well as the complementary ones, an increase in volume is observed in the anterior portion of the mandible, irregular crateriform, painful on palpation. Verrucous carcinoma was diagnosed involving teeth 3.3-4.3 and the surrounding mucosa in the oral cavity. The treatment consisted of complete surgical removal, without alteration or damage to the surrounding areas, with postoperative follow-up. Knowledge of this type of pathology can guide the dentist to the suspicion of different cancerous lesions, which will prevent complications and thus provide the best treatment option for affected patients.